Theoretical and Experimental Studies on the Near‐Infrared Photoreaction Mechanism of a Silicon Phthalocyanine Photoimmunotherapy Dye: Photoinduced Hydrolysis by Radical Anion Generation. Issue 9 (23rd August 2020) - Kobayashi, Masato; Harada, Mei; Takakura, Hideo; Ando, Kanta; Goto, Yuto; Tsuneda, Takao; Ogawa, Mikako; Taketsugu, Tetsuya
Abstract: Invited for this month's cover are the collaborating groups of Dr. Masato Kobayashi and Prof. Mikako Ogawa, both from Hokkaido University, Sapporo, Japan. The cover picture shows the photochemical reaction process of the near‐infrared (NIR) photoimmunotherapy dye IR700, and subsequent cancer cell death. A computational study predicted that ligand dissociation, which is known to initiate cancer cell death, proceeds by the hydrolysis of the IR700 radical anion, rather than as a direct result of NIR irradiation. This mechanism has also been supported by experimental work. Read the full text of the Communication at 10.1002/cplu.202000338 . Abstract : "Near‐infrared (NIR) photoimmunotherapy using the IR700 dye is attracting a great deal of attention because this treatment is less toxic to normal cells and therefore has very few side effects. However, NIR light is not sufficiently biopermeable for effective deep‐tissue cancer treatment". Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/cplu.2012000338 ).